From childhood to senior professional football: elite youth players` engagement in non-football activities - Haugaasen, M.; Toering, T.; Jordet, G. (Journal of Sports Sciences, 2014)
Despite the large amount of research available on how engagement in football practice relates to future performance level among football players, similar information about the contribution of non-football activities is scarce. Based on data from 745 elite youth players this study aimed to identify the characteristics and contribution of diverse participation towards elite youth and senior professional status. The data were collected using a retrospective questionnaire where the players reported the amount of time spent in other sports than football, in addition to their perceived contribution of different non-football activities for developing football skills. The accumulated hours of time spent in other sports of players who had obtained a senior professional contract were compared to non-professional players, using multilevel modelling (n = 558), while a t-test compared the activity ratings to each other. No significant differences were identified between professional and non-professional players` engagement history, but overall, the players rated sports similar to football to be significantly more relevant for developing football skills than other sports. The results suggests that spending time in non-football activities did not contribute to present differences in performance attainment in football, but also that potential advantages of such activities may be related to their characteristics.